2015
DOI: 10.1121/1.4905882
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate emission of bubble streams with killer whale biphonic calls: Perspectives on production and function

Abstract: Stereotyped pulsed calls were attributed to 11 killer whales (Orcinus orca) with and without synchronous bubble streams in three datasets collected from two facilities from 1993 to 2012. Calls with and without synchronous bubble streams and divergent overlapping high frequency components ("biphonic" vs "monophonic") were compared. Subjects produced bubbles significantly more often when calls had divergent high frequency components. However, acoustic features in one biphonic call shared by five subjects provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 9 publications
(26 reference statements)
2
19
0
Order By: Relevance
“…However, bubble streams could also be interpreted as a behavior associated with high states of positive arousal generally. This has been suggested in multiple previous studies on cetaceans, which found bubbles to be associated with higher vocal activity (Dudzinski 1996), "excitement vocalizations" (Herzing 1996), large groups (Pryor 1990), and close-range high-activity states in general (Bowles et al 1988(Bowles et al , 2015.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…However, bubble streams could also be interpreted as a behavior associated with high states of positive arousal generally. This has been suggested in multiple previous studies on cetaceans, which found bubbles to be associated with higher vocal activity (Dudzinski 1996), "excitement vocalizations" (Herzing 1996), large groups (Pryor 1990), and close-range high-activity states in general (Bowles et al 1988(Bowles et al , 2015.…”
Section: Discussionmentioning
confidence: 54%
“…In particular, little is known about beluga whale behaviortheir arctic habitat makes field studies nearly impossible, and they are less common in captive environments than bottlenose dolphins. This research will expand our understanding of a previously unstudied behavior that is known to occur in at least three odontocete species (McCowan and Reiss 1995, Hill et al 2011, Bowles et al 2015. Especially significant for this study are two opportunities.…”
Section: Significance and Implicationsmentioning
confidence: 77%
See 3 more Smart Citations